Prophylaxis of рurulent-septic diseases of postpartum period for high-risk puerperas - A. E. Mitichkin; Yu. E. Dobrokhotova; N. Yu. Ivannikov; V. I. Dimitrova; O. A. Slyusareva; S. A. Khlynova; V. A. Lyubeshkina; A. T. Taalaybekova (Медицинский совет, 2020)
Background. Postpartum purulent-septic diseases are one of the topical issues of modern obstetrics due to high prevalence and absence of downward trend toward reduction in the disease incidence.Objective: improve the management of high risk puerperas to prevent the development of purulent-septic complications in the postpartum period.Materials and methods. The cohort prospective comparative study included 78 puerperas, who experienced spontaneous labour complicated by injuries to birth canals. The patients were divided into two groups according to the risk of developing purulentseptic complications and the management of patients. Group 1, control group, (n = 20) included the puerperas, who did not show any signs of inflammatory diseases of the genital tract during pregnancy. Group 2 included patients, who were diagnosed with various forms of vaginal dysbiosis based on the results of bacterioscopic and bacteriological examination of the genital tract. The group was further divided into two subgroups depending on the type of treatment. Subgroup 1 of Group 2 (n = 28) only received standard hygiene care, and subgroup 2 (n = 30) received standard hygiene procedures combined with vaginal irrigation using benzidamine hydrochloride solution (Tantum Rosa) for 3 days in the obstetric hospital.Results. The study resulted in improving postpartum care of high-risk puerperas to prevent purulent-septic complications. Discussion The test results showed that the use of benzidamine hydrochloride (Tantum Rosa) in the postpartum period prevents the purulent-septic complications of puerperium, such as inflammation and disruption of perineal muscle sutures and endometritis, as well as relieves pain and discomfort, and improves the puerperas’ quality of life.Conclusion: Based on the study results, we recommend the use of this drug in the early postpartum period to prevent purulentseptic complications in the high-risk groups.